Epistemic Sovereignty in Islamic Education under Secular Regulatory Regimes: A Normative–Integrative Framework for Science Education - Suheri Suheri (Al-Qalam Institue, 2025)
This study examines the relationship between secular governance systems and epistemic sovereignty in Islamic education, with particular relevance to contemporary science education. Regulatory frameworks such as accreditation, credential hierarchies, and performance standards are often treated as neutral, yet they shape how knowledge and authority are legitimised. Studies on Islamic education mainly focus on institutional adaptation, with limited attention to how these frameworks transform the epistemological basis of knowledge legitimacy. Using a qualitative library-based approach, this study draws on sociology of knowledge, institutional theory, and Islamic intellectual tradition to analyse the impact of secular standardisation on epistemic authority. The findings indicate that the primary challenge facing Islamic education is not institutional marginalisation but normative relocation, where externally codified benchmarks increasingly define legitimacy. Consequently, internally grounded criteria—such as textual continuity, interpretive discipline, scholarly lineage, and ethical formation—risk losing epistemic primacy. This dynamic is particularly evident in science education, where empirical validation and standardised assessment dominate knowledge evaluation. To address this challenge, the study proposes a normative–integrative framework based on the concept of negotiated primacy. This framework enables Islamic educational institutions to engage with secular governance systems while maintaining the hierarchical primacy of their internal epistemological foundations. The study contributes to broader debates on education, governance, and knowledge by conceptualising epistemic sovereignty as a dynamic and reflexive institutional practice in contemporary educational systems.